Is having a child with special needs a barrier to physical activity? A mixed design study - Melek Kurşunel; Öznur Akpınar; Nazlı Yanar Tunçel; Selahattin Akpınar (PLoS ONE, 2026)
Having special needs is considered a difficult situation in society, but perhaps only families experiencing this situation know how challenging it is to be the parent of a child with special needs. Since families plan their entire lives around their children’s needs, they often neglect their own social lives and free time. The aim of this study is to investigate whether having a child with special needs constitutes a barrier to physical activity for parents, using a mixed methods approach. A total of 212 parents caring for individuals with special needs volunteered to participate in the study. The quantitative part of the study used a questionnaire to collect demographic information, as well as scales to measure perceived barriers to physical activity and care burden, and a shortened version of the international physical activity questionnaire. For the qualitative part of the study, a four-question interview form was used. It was observed that, as participants’ scores for physical activity barriers increased, so did their body mass index and care burden scores (p < 0.05). According to the results of the regression analysis, the model of physical activity barriers and care burden status of parents of children with special needs according to the participants’ metabolic equivalent classification was not significant (p > 0.05). However, the results of the qualitative data analysis revealed four barriers that parents indirectly associated with having a child with special needs hindering physical activity: responsibilities, having a child with special needs, psychological state and problems related to sports facilities. These results suggest that quantitative research methods alone may be insufficient for identifying factors hindering physical activity among individuals with special needs. Future studies may wish to conduct applied research projects on physical activity barriers among parents of children with special needs.